Pandemic Management of Coronavirus Disease of 2019: A Kuwait Perspective on the Example of Al-Adan Hospital - Alhadhoud, Dr. Meshal A; Alsiri, Dr. Najla F; Al-Salem, Dr. Najla; Sibbel, Prof. Rainer (International Journal of Innovative Research in Medical Science, 2021)
Objective: Coronavirus Disease of 2019 (COVID19) as a pandemic could paralyze the operational system of healthcare organizations. However, the crisis management plan of COVID19 implemented in Al-Adan Hospital, Kuwait, has been successful. Therefore, this study aims to present the crisis management plan for COVID19 implemented in our institution. Design: Presenting and framing the prescriptive strategy of the crisis management approach adopted. The literature was further critically reviewed to reflect on the plan implemented to enrich the current experience and formulate future recommendations. Setting: Al-Adan Hospital, Kuwait. Main Outcome Measures: The prescriptive strategy adopted for the crisis management plan consists of three managerial frameworks: COVID19 team, COVID19 management strategy, and strategy for maintaining emergency healthcare services. Results: Balancing between the standardization model of implementing governmental regulations, and the personalization model of placing the patients and the employees at the center of the strategy, could explain the success of the plan. The strategy implemented could be further strengthened by elevating the principles of leaderships and encouraging health digitalization. Conclusion: This study presents a novel framework of crisis management for healthcare systems by raising the concept of balancing between the standardization and personalization models.